CD317 mediates immunocytolysis resistance by RICH2/cytoskeleton-dependent membrane protection. (January 2021) - Cheng, Jian; Liu, Zhao; Deng, Tian; Lu, Zhen; Liu, Maoxuan; Lu, Xiaoxu; Adeshakin, Funmilayo Oladunni; Yan, Dehong; Zhang, Guizhong; Wan, Xiaochun
Highlights: CD317 protects cancer cells from immunocytolysis by maintaining membrane integrity in response to perforin. CD317 mediates membrane protection through RICH2/cytoskeleton-dependent manner. Knockdown of CD317 or RICH2, or disruption of cytoskeleton strikingly increases the tumor sensitivity to immunocytolysis. Abstract: Immune evasion is a common hallmark of cancers. Immunotherapies that aim at restoring or increasing the immune response against cancers have revolutionized outcomes for patients, but the mechanisms of resistance remain poorly defined. Here, we report that CD317, a surface molecule with a unique topology that is double anchored into the membrane, protects tumor cells from immunocytolysis. CD317 knockdown in tumor cells renders more severe death in response to NK or chimeric antigen receptor-modified NK cells challenge. Such effects of CD317 silencing might be the results of increasing sensitivity of tumor cells to immune killing rather than strengthening immune response, since neither effector-target cell contact nor the activation of effector cells was affected, and the enhanced cytolysis was also not counteracted by the addition of recombinant CD317 proteins. Mechanistically, CD317 might endow tumor cells with more flexibility to modulate cytoskeleton through its association with RICH2, thereby protects membrane integrity against perforin and consequently promotes survival in response to immunocytolysis. These results reveal a new mechanism of immunocytolysis resistance and suggest CD317 as an attractive target which can be exploited for improving the efficacy of cancer immunotherapies.